Corporate culture: The perceptions of personnel managers in South Africa - J. Viljoen (South African Journal of Business Management, 1987)
In this paper some core dimensions along which corporate culture can be analysed are identified. It is argued that, for large scale studies of corporate culture, personnel managers are the most appropriate sampling base. Using a mailed questionnaire a sample of 199 South African companies was surveyed in order to isolate their cultural attributes as perceived by the personnel manager. The research findings revealed: (i) a strong association between strategic management style and perceived culture strength; (ii) greater perceived performance potential and better labour relations amongst strong culture companies, and (iii) significant differences in perceived culture strength between managerial and non-managerial employees. The implications of these findings are discussed.
Keywords: 650